2013
DOI: 10.1371/journal.pone.0065257
|View full text |Cite
|
Sign up to set email alerts
|

Combining mTOR Inhibition with Radiation Improves Antitumor Activity in Bladder Cancer Cells In Vitro and In Vivo: A Novel Strategy for Treatment

Abstract: PurposeRadiation therapy for invasive bladder cancer allows for organ preservation but toxicity and local control remain problematic. As such, improving efficacy of treatment requires radiosensitization of tumor cells. The aim of study is to investigate if the mammalian Target of Rapamycin (mTOR), a downstream kinase of the phosphatidylinositol 3-kinase (PI3K)/AKT survival pathway, may be a target for radiation sensitization.Experimental DesignClonogenic assays were performed using 6 bladder cancer cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Although the use of mTOR inhibitors in this context is exciting due to its availability for clinical trials and evidence suggesting tumor radiosensitization with mTOR inhibition (4146), this must be tempered by the previously observed toxicities of mTOR inhibitors (18). One adverse event in particular, reversible pneumonitis, is of obvious concern, but appears to be dosing sensitive and completely reversible with treatment cessation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of mTOR inhibitors in this context is exciting due to its availability for clinical trials and evidence suggesting tumor radiosensitization with mTOR inhibition (4146), this must be tempered by the previously observed toxicities of mTOR inhibitors (18). One adverse event in particular, reversible pneumonitis, is of obvious concern, but appears to be dosing sensitive and completely reversible with treatment cessation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inhibition of these Akt-associated pro-survival signaling pathways enhances the radiosensitivity to RT of various cancers (12)(13)(14)(15). This improvement may be due to, firstly, the antifungal characteristics of rapamycin itself, and secondly, to the excessive autophagy induced by rapamycin (15). In addition, Liu et al (22) demonstrated that leukemia inhibitory factor (LIF) activated p70 S6 kinase (p70S6K) and its downstream molecules, GSK3α/β, thus leading to the proliferation of NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mTOR can decrease the kinase activity of GSK3β, responsible for the degradation of cyclin D1 (11). Previous studies have shown that mTOR inhibition improves the radiosensitivity of prostate, breast, bladder and brain cancer (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Nassim et al reported an increase of both G1 and G2/M when combining everolimus with radiation in bladder cancer cells (44). They suggest that the everolimusinduced G1 arrest confers an enhanced sensitivity for the following radiation as fewer cells were counted in the rather radioresistant S-phase (45) Equal amounts of protein were separated on SDS gels and the indicated molecules detected after western blotting.…”
Section: Combined Effect Of Temsirolimus and Irradiationmentioning
confidence: 96%